Are local climate adaptation policies credible? A conceptual and operational assessment framework. Issue 3 (2nd September 2019) - Olazabal, Marta; Galarraga, Ibon; Ford, James; Sainz De Murieta, Elisa; Lesnikowski, Alexandra
ABSTRACT: After the Paris Agreement that put stronger emphasis on the development of climate change adaptation policies and on the definition of financing mechanisms, there is a patent need to track whether actual planning efforts are proving sufficient. This entails the development of assessment methods and metrics as plans are drafted and actions implemented. To this end, this paper explores the concept of credibility as a critical issue in climate policy and develops an Adaptation Policy Credibility (APC) conceptual and operational assessment framework for helping to allocate public funding and private investments, and for implementing and catalysing climate policy. Through a pilot testing in four early-adopting cities (Copenhagen, Durban, Quito and Vancouver), a clear potential for large-n tracking and assessment exercises of local climate adaptation plans is envisaged. The APC approach might also be useful to guide individual cities that aim to improve their adaptation planning and policy-making processes.